Analisis Kepuasan Pelanggan Dengan Metode Customer Satisfaction Index (CSI) (Studi Kasus Pada BNI UNIMED) - Sabda Dian Nurani Siahaan; Fauzia Agustini (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of this research is to find out the service quality and customer satisfaction at Bank Negara Indonesia (BNI), Universitas Negeri Medan (UNIMED). The service quality is a very important factor to provide customer satisfaction. This study uses primary data by disseminating questionnaires directly to the sample. In measuring service quality factors, the SERVQUAL model is used, which consists of 5 indicators, Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This research was conducted with a quantitative descriptive approach and the Customer Satisfaction Index (CSI) method. The population in this study is students of Universitas Negeri Medan who are customers of BNI UNIMED. Samples in this study as many as 325 respondents, with sampling techniques Cluster Random Sampling. The results showed the Customer Satisfaction Index (CSI) obtained was 66% which is in the category of Satisfied